Downstream effects of stream flow diversion on channel characteristics and riparian vegetation in the Colorado Rocky Mountains, USA. Issue 5 (4th October 2014) - Caskey, Simeon T.; Blaschak, Tyanna S.; Wohl, Ellen; Schnackenberg, Elizabeth; Merritt, David M.; Dwire, Kathleen A.
Abstract Flow diversions are widespread and numerous throughout the semi‐arid mountains of the western United States. Diversions vary greatly in their structure and ability to divert water, but can alter the magnitude and duration of base and peak flows, depending upon their size and management. Channel geometry and riparian plant communities have adapted to unique hydrologic and geomorphic conditions existing in the areas subject to fluvial processes. We use geomorphic and vegetation data from low‐gradient (≤3%) streams in the Rocky Mountains of north‐central Colorado to assess potential effects of diversion. Data were collected at 37 reaches, including 16 paired upstream and downstream reaches and five unpaired reaches. Channel geometry data were derived from surveys of bankfull channel dimensions and substrate. Vegetation was sampled using a line‐point intercept method along transects oriented perpendicular to the channel, with a total of 100 sampling points per reach. Elevation above and distance from the channel were measured at each vegetation sampling point to analyze differences in lateral and vertical zonation of plant communities between upstream and downstream reaches. Geomorphic data were analyzed using mixed effects models. Bankfull width, depth, and cross‐sectional area decreased downstream from diversions. Vegetation data were analyzed using biological diversity metrics, richness, evenness and diversity, as well as multivariate community analysis. Evenness increased downstream from diversions, through reduced frequency of wetland indicator species and increased frequency of upland indicator species. Probability of occurrence for upland species downstream of a diversion increases at a greater rate beginning around 0·5 m above active channel. The results suggest that channel morphology and riparian plant communities along low‐gradient reaches in montane environments in the Colorado Rocky Mountains are impacted by diversion‐induced flow alteration, with the net effect of simplifying and narrowing the channel and homogenizing and terrestrializing riparian plant communities. Copyright © 2014 John Wiley & Sons, Ltd.